2019
DOI: 10.7554/elife.45590
|View full text |Cite
|
Sign up to set email alerts
|

TRPC3 is a major contributor to functional heterogeneity of cerebellar Purkinje cells

Abstract: Despite the canonical homogeneous character of its organization, the cerebellum plays differential computational roles in distinct sensorimotor behaviors. Previously, we showed that Purkinje cell (PC) activity differs between zebrin-negative (Z–) and zebrin-positive (Z+) modules (Zhou et al., 2014). Here, using gain-of-function and loss-of-function mouse models, we show that transient receptor potential cation channel C3 (TRPC3) controls the simple spike activity of Z–, but not Z+ PCs. In addition, TRPC3 regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 71 publications
8
66
0
Order By: Relevance
“…For this reason, we compared spike firing rates of Purkinje cells in control and L7-SK2 mice that are located in lobules III and X so as to reach spike firing rate homogeneity within these groups. We observed that the genotype alone had no significant effect on the simple spike frequency (two-way ANOVA genotype effect: p = 3.29, F [1,83] = 0.964). However, there was a lobule effect (p = 0.028, F[1, 83] = 5.01): the spike frequency was higher in lobule III than in lobule X Purkinje cells in control mice (lobule III: 81.6 ± 10.0 Hz, n = 20; lobule X: 46.7 ± 4.7 Hz, n = 22; Least Significant Difference (LSD) post hoc test, p = 0.0012; Fig 2F).…”
Section: Membrane Excitability Of L7-sk2 Purkinje Cells Is Enhanced Wmentioning
confidence: 75%
“…For this reason, we compared spike firing rates of Purkinje cells in control and L7-SK2 mice that are located in lobules III and X so as to reach spike firing rate homogeneity within these groups. We observed that the genotype alone had no significant effect on the simple spike frequency (two-way ANOVA genotype effect: p = 3.29, F [1,83] = 0.964). However, there was a lobule effect (p = 0.028, F[1, 83] = 5.01): the spike frequency was higher in lobule III than in lobule X Purkinje cells in control mice (lobule III: 81.6 ± 10.0 Hz, n = 20; lobule X: 46.7 ± 4.7 Hz, n = 22; Least Significant Difference (LSD) post hoc test, p = 0.0012; Fig 2F).…”
Section: Membrane Excitability Of L7-sk2 Purkinje Cells Is Enhanced Wmentioning
confidence: 75%
“…With the various classes of interneurons following the zonal scheme (Consalez and Hawkes, 2013), and the data presented in this study, it could be that Purkinje cells use developmental mechanisms to establish their own behaviorally relevant specializations, and for basket cells, this means their segregation into size-specific zones. It is suggested that Purkinje cells zones may have discrete requirements during LTD (long-term depression) versus LTP (long-term potentiation) (Wu et al, 2019). ZebrinII-positive zones are predicted to have a major role in behaviors such as the vestibulo-ocular reflex, which is heavily dependent upon LTP, whereas as behaviors such as eye-blink conditioning may be more dependent on LTD. We know that at least some portion of the eye blink conditioning circuit is restricted to zebrinII-negative zones (Attwell et al, 1999; Attwell et al, 2001; Mostofi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, since basket cells contribute to the excitation/inhibition (E/I) balance, and since glutamate spillover from climbing fibers impacts molecular layer interneuron function (Szapiro and Barbour, 2007), it is possible that the different sizes of basket cell projections (namely their pinceux, although likely their full innervation) uniquely complement the excitatory innervation. Together, they could drive cerebellar module function (Wu et al, 2019) and synchronous activity (Welsh et al, 1995), but also direct the precision of synaptic plasticity (Wadiche and Jahr, 2005; Paukert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous functions of TRPC3 that have been deduced from the phenotype of TRPC3-deficient mice. One of the most striking effects is an impaired motor coordination that is linked to the strong expression of TRPC3 and its activation by phospholipase C (PLC)-coupled metabotropic glutamate receptors in a specific pool of cerebellar Purkinje neurons [3,4] and was confirmed by a similar effect in a mutant "moonwalker" mouse strain that carries a point mutation in the TRPC3-encoding gene [5]. Despite these and other data demonstrating that TRPC3 mediates a plethora of effects in the context of G-protein-or receptor tyrosine kinase-mediated signalling, its validation as a pharmacological target is still ongoing [6].…”
Section: Introductionmentioning
confidence: 99%